Management of Intracerebral Hemorrhage: Looking to the Future - Vinall, Maria (MD Conference Express, 2009)
The majority of the cell death after hemorrhage occurs around hematomas. It has been theorized that this is partially related to oxidative stress. This article discusses insights from animal models of oxidative stress that may provide potential treatment targets for intracerebral hemorrhage (ICH), hematopoietic stem cell transplantation, and the available neuromonitoring measures and what new measures need to be developed for ICH.